Research-Based Theater and “Stigmatized Trauma”: The Case of Suicide Bereavement - Silvén Hagström, Anneli (Frontiers in Psychology, 2020)
Background: Existing research shows that family members who suffer the loss of a loved one through suicide often experience self-blame and shame, and that this limits their grieving process. It can also lock them into stigmatized positions and the notion that either somebody or a dysfunctional family is to blame for the suicide. Aim: This article investigates from a narrative perspective how a theater play might counteract the stigma that surrounds suicide bereavement by contributing destigmatizing understandings of suicide. Methods: A theater play was performed in a churchyard theater in Stockholm, Sweden, in 2019. Audience members were asked to write down their free reflections on a form distributed at the theater. In particular, they were asked to assess whether they found the play related to their own lives and, if so, how; and to describe what they had learned. Their written reflections [N=41] were analyzed from a narrative methodological perspective to investigate their responses to the play. Three categories of audience member were identified from their responses: people with their own suicide bereavement experiences; people with similar but different experiences of stigmatized trauma; and people who did not report any experiences of suicide or stigmatized trauma. Results: The suicide-bereaved generally reported familiarity with the thematic performed, in particular the “why question”, the blame and shame responses and the silenced family communication. Most of these aspects were also shared by those affected by other types of stigmatized trauma. Respondents from all categories emphasized how they had learned that suicide is a desperate rather than a deliberated act, caused by overwhelming emotional pain or depression. Ultimately, suicide was perceived as an involuntary act caused by complex interacting factors linked to both inner vulnerabilities and stressful life events, for which no one was to blame. Conclusions: The results show that research-based theater is a time-limited and cost-effective method of introducing alternative meanings and identities to both individual mourners and the broader cultural context from which stigma originates, and how it can have destigmatizing effects on a stigmatized trauma such as suicide bereavement.